Is management of risk sharing by banks a cause for bank runs? - H. Abraham (South African Journal of Business Management, 2010)
A bank, acting as a central planner under aggregate full certainty, optimizes liquidity allocation by sharing risk between discrete number of depositors. This paper demonstrates the following. (a) It is sufficient to rule out a bank run if all depositors inform the bank their types, patient or impatient, in advance, in a noncommittal manner. There cannot be a bank run because depositors' strategic behaviour induces the bank to act as a central planner under aggregate full certainty. (b) The impossibility of a bank run is consistent with the price mechanism in partial equilibrium; but it may be inconsistent with the price mechanism in general disequilibrium. (c) The paper concludes that the management of risk sharing by banks is not a cause for bank runs.
Keywords: 650